Community Preparedness for Flood Disasters in Karang Intan District as a Social Sciences Learning Resource - Amitasari, Noor; Wahyu, Wahyu; Arisanty, Deasy; Nugroho Putro, Herry Porda; Arifin Anis, Moh Zaenal (Universitas Lambung Mangkurat, 2024)
The problem of flooding needs the attention of all parties. The impacts caused by flooding are numerous, and almost all aspects of people's lives are disrupted. This research aims to determine the causes of floods, community preparedness for flood disasters, and flood disasters as a social study learning resource. The research uses a qualitative approach with descriptive methods. Namely, it is a process that observes, analyses, and describes phenomena regarding community preparedness for flood disasters in Karang Intan District as a social study learning resource. The results of the research show (1) The cause of the flooding that occurred in Jingah Habang Ulu and Jingah Habang Ilir Villages, Karang Intan District, Banjar Regency was high rainfall with long intensity with heavy rain for quite a long time, rivers close to residents' settlements overflowed due to water being delivered and rubbish along riverbanks and shallow rivers (2) Community preparedness for flood disasters in Jingah Habang Ulu and disasters in Jingah Habang Ilir Villages, Karang Intan District, Banjar Regency is to provide signs from the early warning system of floods such as high rainfall, so areas with high levels report if conditions water overflows into low areas to be alert, mobilize residents using rubber boats, create emergency posts, secure valuables in safer or higher places by making anangs from blocks, bamboo or galam wood, (3) Flood disaster preparedness as The source of social studies learning is by implementing learning in schools regarding learning material regarding preparedness which is included in natural disaster mitigation material. Based on the research results, it can be concluded that flood disasters occur due to natural and human factors. It is hoped that the flood disaster will receive a response from all parties so that it can become a solution to reduce the risk of flooding. Schools insert flood disaster preparedness material as a learning resource so that students can know about flood disaster preparedness if it occurs in their environment.